2008
DOI: 10.1007/978-1-60327-214-8_1
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Germline Stem Cells in Drosophila

Abstract: SummaryGermline stem cells (GSCs) in Drosophila are a valuable model to explore of how adult stem cells are regulated in vivo. Genetic dissection of this system has shown that stem cell fate is determined and maintained by the stem cell's somatic microenvironment or niche. In Drosophila gonads, the stem cell niche-the cap cell cluster in females and the hub in males-acts as a signaling center to recruit GSCs from among a small population of undifferentiated primordial germ cells (PGCs). Shortrange signals fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
97
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 129 publications
2
97
0
Order By: Relevance
“…This process is known to depend on Piwi expression only in somatic cells forming the GSC niche at the anterior-most end of the germarium (2, 6). The GSC niche consists of the terminal filament, escort cells, and cap cells, which directly associate with GSCs via adherens junctions (11,30). In the WT germarium, Piwi is known to be strongly stained in the nuclei of niche cells and GSCs, weakly stained in cystoblasts and early mitotic cysts, and strongly stained in late mitotic and differentiating 16-cell cysts (3,6).…”
Section: Loss Of Nuclear Piwi Localization Does Not Affect Stem Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is known to depend on Piwi expression only in somatic cells forming the GSC niche at the anterior-most end of the germarium (2, 6). The GSC niche consists of the terminal filament, escort cells, and cap cells, which directly associate with GSCs via adherens junctions (11,30). In the WT germarium, Piwi is known to be strongly stained in the nuclei of niche cells and GSCs, weakly stained in cystoblasts and early mitotic cysts, and strongly stained in late mitotic and differentiating 16-cell cysts (3,6).…”
Section: Loss Of Nuclear Piwi Localization Does Not Affect Stem Cellmentioning
confidence: 99%
“…Although several suppressors of piwi mutations restoring GSC maintenance were identified (7)(8)(9)(10), the key niche signal regulated by piwi remains unknown (reviewed in refs. 11,12). It was also shown that the intrinsic expression of Piwi in GSCs promotes their mitotic divisions (3,6).…”
mentioning
confidence: 99%
“…Specification of primordial germ cells (PGCs) in the developing Drosophila embryo requires maternal inheritance of cytoplasmic factors that are concentrated in the posterior pole in an area known as the pole or germ plasm (Ephrussi and Lehmann 1992;Jongens et al 1992;Williamson and Lehmann 1996;Houston and King 2000;Mahowald 2001;Strome and Lehmann 2007;Bastock and St Johnston 2008;Dansereau and Lasko 2008). Pole plasm contains electron-dense granules and related amorphous material that is rich in ribonucleoproteins and mitochondria; it is related to nuage, which surrounds the nurse cell nuclei and contains some of the same components (Dansereau and Lasko 2008;Chuma et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Pole plasm contains electron-dense granules and related amorphous material that is rich in ribonucleoproteins and mitochondria; it is related to nuage, which surrounds the nurse cell nuclei and contains some of the same components (Dansereau and Lasko 2008;Chuma et al 2009). Similar electron-dense amorphous material often in close apposition to mitochondria is found in the cytoplasm of germ cells in various species and is known as P granules in C. elegans, germinal granules in Xenopus, and intermitochondrial cement and chromatoid bodies in mice (Dansereau and Lasko 2008;Chuma et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation